Mixed potential sensors using lanthanum manganate and terbium yttrium zirconium oxide electrodes - Brosha, Eric L.; Mukundan, Rangachary; Brown, David R.; Garzon, Fernando H. (Sensors and actuators. B, Chemical, 2002)
We have demonstrated a mixed potential, zirconia electrolyte-based sensor that utilizes dense, thin films of LaMnO 3 and Y 0.16Tb 0.30Zr 0.54O 2 − as electrodes to generate an EMF that is proportional to the oxidizable gas species (CO, C 3H 6, and C 3H 8) concentration in a gas stream containing oxygen. The devices reported in this work were tested at 600 and 700 °C and in gas mixtures with O 2 concentrations between 0.86 and 1.75%. An Au/LaMnO 3/YSZ/Y 0.16Tb 0.30Zr 0.54O 2 −/Au device was tested for a total of 3000 h at 600 and 700 °C and was subject to periodic excursions to 10 −10 atm PO 2 to simulate reducing conditions. SEM analysis indicated that the aging effects measured in the device response over the course of this experiment may be linked to the sintering of the Au pad used for current collection on the metal oxide electrode. Three-terminal devices were fabricated so that the magnitude of the mixed potential generated from CO and C 3H 6 exposure on the Au/Y 0.16Tb 0.30Zr 0.54O 2 −, Pt/Y 0.16Tb 0.30Zr 0.54O 2 −, Au/LaMnO 3, and Pt/LaMnO 3 metal/metal oxide electrode combinations could be studied at 600 °C and in 1% O 2. It was found that the catalytic properties of the Au or Pt used for current collection played a significant role in the generation of the mixed potential for both metal oxides tested. The combination of Pt on LaMnO 3 gave an equilibrium response whereas a significant mixed potential was generated on both Au/Y 0.16Tb 0.30Zr 0.54O 2 − and Au/LaMnO 3 electrodes at 600 °C.